Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Research on design and applications of multistable mechanical metamaterial structures with high fatigue resistance - Song Gao; Meiling Zhang; Lang Yu; Jinkui Chu; Jianwei Sun; Luquan Ren (Engineering Structures, 2026)

Tectonic subsidence at a fault intersection and its control on sediment accumulation in the Bohai Sea, eastern China - Wenqin Jiang; Weiguo Hou; Hongxian Chu; Yuekai Hao; Wang Song; Meiling Yin; Qingtong Wang (Marine Geology, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

SREBP1-activated lipid metabolism drives ferroptosis and progression of clear cell renal cell carcinoma - Bao Wang; Junpeng Fu; Jian Qian; Yuang Wei; Meiling Bao; Haoqi Miao; Xinzhe Zhao; Kezheng Shao; Yuan Song; Ruoyun Tan; Jie Li; Pengfei Shao (Science China Life Sciences, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Long-term nitrogen enrichment affects soil organic carbon fractions through microbial pathways in fluvo-aquic soil - Binggeng YANG; Jiwen CUI; Meiling ZHANG; Kangrui FANG; Chao AI; Tengfei GUO; Shaomin HUANG; Dali SONG; Wei ZHOU (Pedosphere, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

Bacteriochlorophyll reveals estuarine hypoxia and anoxygenic photosynthetic carbon fixation - Jiawei Kan; Liqin Duan; Jinming Song; Meiling Yin; Xuegang Li; Xiaoqi Liu; Huamao Yuan; Yingxia Wang (Limnology and Oceanography, 2025)
Bacteriochlorophylls (Bchls) are photosynthetic pigments produced by aerobic anoxygenic photosynthetic bacteria and anoxygenic photosynthetic bacteria. However, the sources, degradation, and influence of redox conditions in marine environments remain unclear. This study investigated the distribution of Bchls in the Changjiang Estuary to evaluate their origins, degradation, and environmental response. Results showed that total bacteriochlorophylls a (T Bchl a ), including bacteriochlorophyll a (Bchl a ) and its degradation product bacteriopheophytin a (Bphe a ), were higher in surface waters than in bottom waters in the inner estuary, where microbial evidence ( Sphingomonadaceae ) identified aerobic anoxygenic photosynthetic bacteria as the dominant source of T Bchl a . In contrast, the outer estuary exhibited elevated T Bchl a in bottom waters, with purple sulfur bacteria ( Chromatiaceae and Ectothiorhodospiraceae ) as the primary contributors. Significant negative correlations between Bphe a concentrations in bottom seawaters and surface sediments and the dissolved oxygen levels in bottom waters, along with a positive correlation between Bphe a in the surface sediments and the salinity difference between bottom and surface seawaters (Δ S ), suggest that Bphe a may serve as a useful indicator of hypoxia and water stratification. The contribution of anoxygenic photosynthetic bacteria to carbon fixation is expected to increase notably, potentially reaching 16% of phytoplankton carbon fixation after 100 years under expanding hypoxia. These findings establish Bchls as reliable indicators of hypoxia and water stratification and provide a framework for reevaluating carbon fixation in global hypoxic coastal systems.

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

Divergent mitigation mechanisms of soil antibiotic resistance genes by biochar from different agricultural wastes - Yu Yao; Peiyang Yang; Bin Wang; Qiao Xu; Fanhao Song; Yabo Wang; Yingdong Zhao; Lei Guo; Xiaozhi Wang; Meiling Xu (Environmental Pollution, 2025)

Detection of whey protein concentrate adulteration using laser-induced breakdown spectroscopy combined with machine learning - Meiling Zhu; Weiran Song; Xuan Tang; Xiangzeng Kong (Food Additives & Contaminants: Part A, 2025)

Unraveling the trisubstrate-triproduct reaction mechanisms of wine grape VvCYP76F14 to improve wine bouquet - Zhizhong Song; Meiling Tang; Huilin Xiao; Houhua Xu; Matthew Shi; Adeeba Dark; Zhenqiang Xie; Bin Peng (Food Chemistry, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

A lightweight fine-grained pelagic fish recognition algorithm based on object detection - Weiyu Ren; Dongfan Shi; Yifan Chen; Liming Song; Qingsong Hu; Meiling Wang (Aquaculture International, 2025)

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Investigating CO₂ sequestration via enhanced rock weathering: Effects of temperature and citric acid on dolomite and basalt - Qiao Xu; Feifan Zhang; Fanhao Song; Hongyan Guo; Xiaozhi Wang; Fenfen Bi; Meiling Xu (Journal of Cleaner Production, 2024)

m6A-mediated HDAC9 upregulation promotes particulate matter-induced airway inflammation via epigenetic control of DUSP9-MAPK axis and acts as an inhaled nanotherapeutic target - Yingying Zeng; Xin Bai; Guiping Zhu; Mengchan Zhu; Wenjun Peng; Juan Song; Hui Cai; Ling Ye; Cuicui Chen; Yuanlin Song; Meiling Jin; Xue-Qing Zhang; et al. (Journal of Hazardous Materials, 2024)

Nanoarchitectonics of bamboo-based heterojunction photocatalyst for effective removal of organic pollutants - Xiaole Yan; Meiling Chen; Junning Wang; Zhaodong Wang; Ruiqi Xin; Dujuan Wu; Ye Song; Song Li; Wenkai Zhu; Chaohai Wang; Yanli Mao (Chemical Engineering Journal, 2024)

Calcium polypeptide mitigates Cd toxicity in rice via reducing oxidative stress and regulating pectin modification - Hongbing Chen; Xiaojun Tang; Tiejun Wang; Weifang Liao; Zhixian Wu; Meiling Wu; Zhihao Song; Yadong Li; Pan Luo (Plant Cell Reports, 2024)

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

Vertical variations of bacteriohopanepolyols near the Changjiang Estuary waters: Implications for marine hypoxia and bacterial activities - Meiling Yin; Liqin Duan; Jinming Song; Jiawei Kan; Huamao Yuan; Xuegang Li; Yingxia Wang (Chemical Geology, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Unraveling seasonal shifts in microbial and geochemical mediated arsenic mobilization at the estuarine sediment-water interface under redox changes - Liqin Duan; Jinming Song; Yuting Zhang; Meiling Yin; Huamao Yuan; Xuegang Li (Science of The Total Environment, 2024)

Metagenomic binning analyses of swine manure composting reveal mechanism of nitrogen cycle amendment using kaolin - Huakang Li; Zixuan Zhao; Meiling Shi; Bin Luo; Guangdong Wang; Xiaojuan Wang; Jie Gu; Zilin Song; Yifan Sun; Li Zhang; Jia Wang (Bioresource Technology, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Amino-functionalized nanocellulose aerogels for the superior adsorption of CO2 and separation of CO2/CH4 mixture gas - Wenkai Zhu; Meiling Chen; Jieun Jang; Minsu Han; Yeonggyun Moon; Junghwan Kim; Jungmok You; Song Li; Teahoon Park; Jeonghun Kim (Carbohydrate Polymers, 2024)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Impacts of shipyard oil leakage on the PAHs and PCBs occurrence in Xiangshan Bay, China - Yi Luo; Ganghui Tong; Qingbin Song; Peiran Tao; Meng Jin; Nitao Gu; Meiling Zheng; Xinwei Yu; Xubiao Yu (Marine Environmental Research, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Neuroplasticity Following Stroke from a Functional Laterality Perspective: A fNIRS Study - Ying Song; ZhiFang Sun; WeiZhen Sun; MeiLing Luo; YiJun Du; Jing Jing; YongHui Wang (Brain Topography, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

North-south differences in hypoxia and nitrogen cycle of the East China Sea over the last century indicated by sedimentary bacteriohopanepolyols - Meiling Yin; Jinming Song; Liqin Duan; Huamao Yuan; Xuegang Li; Quancai Peng (Chemical Geology, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

First detection of the occurrence and study of the genetic diversity of novel putative kirkoviruses in donkey in China - Panpan Tong; Haifeng Deng; Liya Duan; Meiling Ren; Xiaozhen Song; Hao Wang; Duishanbayi Gulimire; Ling Kuang; Jinxin Xie (Virus Genes, 2022)

Effects of Epichloë endophytes on litter decomposition--depending on different host species - Meiling Song; Yuqin Wang; Hongsheng Wang; Gensheng Bao; Xiuzhang Li (Plant and Soil, 2022)

Epichloë endophyte infection enhances the tolerance of Stipa purpurea to parasitic stress through the regulation of antioxidants and phytohormones - Gensheng Bao; Meiling Song; Yuqin Wang; Yali Yin (Plant and Soil, 2021)

Identification and genomic characterization of emerging CRESS DNA viruses in thoroughbred horses in China - Panpan Tong; Meiling Ren; Xinlong Xu; Xiaozhen Song; Lei Zhang; Ling Kuang; Jinxin Xie (Virus Genes, 2021)

First detection and genetic characterization of equid herpesvirus 2, 4, and 5 in China - Jinxin Xie; Panpan Tong; Lei Zhang; Meiling Ren; Xiaozhen Song; Chenyang Jia; Nuerlan Palidan; Li Zhang; Ling Kuang (Archives of Virology, 2021)

Proteomic Analysis of Serum Differentially Expressed Proteins Between Allergic Bronchopulmonary Aspergillosis and Asthma - Hui Cai; Diquan Shuai; Xiaomin Xue; Yuqing Mo; Xixi Song; Ling Ye; Shuiming Li; Daiwei Wang; Yun Wang; Meiling Jin (Mycopathologia, 2021)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Discovery and characterization of a stable lipase with preference toward long-chain fatty acids - Meiling Chen; Xiuzhen Gao; Wu Yang; Caili Sun; Junhuan Yang; Huaiyuan Zhang; Yuanda Song (Biotechnology Letters, 2020)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Interactive effects of Epichloë fungal and host origins on the seed germination of Achnatherum inebrians - Gensheng Bao; Meiling Song; Yuqin Wang; Kari Saikkonen; Hongsheng Wang (Symbiosis, 2019)

Structure and geochronology of the Tongbai complex and their implications for the evolution of the Tongbai orogenic belt, central China - Huan Liu; Shoufa Lin; Chuanzhong Song; Meiling Wu (International Geology Review, 2017)

Identification and expression analysis of BoMF25, a novel polygalacturonase gene involved in pollen development of Brassica oleracea - Meiling Lyu; Ying Liang; Youjian Yu; Zhiming Ma; Limin Song; Xiaoyan Yue; Jiashu Cao (Plant Reproduction, 2015)

An asexual Epichloë endophyte modifies the nutrient stoichiometry of wild barley (Hordeum brevisubulatum) under salt stress - Meiling Song; Qing Chai; Xiuzhang Li; Xiang Yao; Chunjie Li; Michael J. Christensen; Zhibiao Nan (Plant and Soil, 2015)